Nutrition and physical activity [ (VEA Australia Pty Ltd, 2006)
Research suggests we should be physically active for at least 30 minutes a day. This program, featuring interviews with dieticians from the Australian Institute of Sport, looks at the importance of nutrients in our diet to support physical activity. The functions of various foods are outlined and students will develop an understanding of how nutrients and physical activity go hand in hand for overall performance.